Pemilihan Presiden 2004 dan Kualitas Demokrasi - Bambang Cipto (Universitas Islam Indonesia, 2004)
The direct presicent election in 2004 have a-unique aspect according to the change of democratitation, not just because this is the first time people choose directly their own president, but this is alo a transition of democracy in Indonesia which will shows how good the quality of our democracy. In this election candidate should have